Recurrent, atraumatic acute compartment syndrome secondary to IgA vasculitis: A case report - Mel Ebeling; Blake Hudson (Journal of the American College of Emergency Physicians Open)
Abstract Acute compartment syndrome is a surgical emergency requiring rapid recognition in the emergency department to minimize morbidity and mortality. It is most commonly caused by traumatic extremity fractures, which account for about 75% of cases. Atraumatic acute compartment syndrome is substantially less common with current evidence mostly limited to case reports, and diagnosis is made more challenging by the absence of an obvious traumatic injury. We present the case of a young adult female patient with IgA vasculitis who developed recurrent, atraumatic acute compartment syndrome and was successfully managed with prompt fasciotomy. This is the first case of spontaneous intramuscular hemorrhage, a rare sequela of IgA vasculitis, leading to recurrent, atraumatic acute compartment syndrome. This case highlights the importance of both a thorough physical exam and maintaining a high suspicion for acute compartment syndrome in the absence of injury to ensure patients receive prompt surgical evaluation for definitive care.